CAUT report. - Rimmington, G. M. ([University of Melbourne], 1995)
This is a final report for a 1995 National Teaching Development Grant funded by the Committee for the Advancement of University Teaching. The report outlines the major objectives and achievement of the project and suggests applications for the new computer-assisted learning packages.